Comparison of Virtual Reality Therapy and Conventional therapy on upper limb function and Ocular Tracking on individuals with Parkinson's Disease : a single Blind Randomized Control Study - Mothabeng, D. Joyce (University of Pretoria, 2017)
Dissertation (MPhysiotherapy)--University of Pretoria, 2016.